Peningkatan Motivasi Belajar Siswa melalui Keterampilan Mengajar Guru di Sekolah Dasar - Siti Komala Putri; Sofian Abdulatif; Annisa Dwi Hamdani; Chendi Maulana Baharudin Yusup; Acep Iyan (Journal on Education, 2022)
Humans can not be separated from learning. A person will definitely go through a period in life when he needs to study. The learning can be formal or informal. Elementary school is a place to learn and acquire knowledge at an early level which can be the foundation for students. The problem now is that many students are less enthusiastic about learning, get bored quickly to carry out learning. In this case the teacher must be able to increase students' interest in learning. The aim of this study is to analyze student learning motivation that develops through the teaching competence of teachers in the classroom. The research method uses descriptive qualitative. The data collection technique was carried out based on the results of the interviews. The results showed that the teaching skills of teachers had a partial positive effect on students' learning motivation. So that student learning motivation can be increased by improving the teaching skills of elementary school teachers.